(untitled) (Social Science Review, 2025)
This paper explores the relationship between factor price ratios and factor intensities during the period of rapid spread of high yield variety (HYV) technology of cereal production in Bangladesh agriculture. The theory of induced innovation suggests that an increase in the relative price of a factor would lead farmers to adopt technologies that minimize the usage of that factor, and conversely. However, available data from Bangladesh agriculture indicate that although the price of fertilizer, a key factor in HYV cultivation, relative to land and labor, rose substantially during the study period, the fertilizer-labor and fertilizer-land intensities in cultivation also rose very steeply. It is shown that minimizing the use of the expensive factor is neither necessary nor sufficient for profit maximization in agricultural production. Social Science Review, Vol. 41(1), June 2024, Page 179-194.